Two Approaches to Focus Group Data Collection for Qualitative Health Research - Rachel Flynn; Lauren Albrecht; Shannon D. Scott (International Journal of Qualitative Methods, 2018)
This article discusses four challenges to conducting qualitative focus groups: (1) maximizing research budgets through innovative methodological approaches, (2) recruiting health-care professionals for qualitative health research, (3) conducting focus groups with health-care professionals across geographically dispersed areas, and (4) taking into consideration data richness when using different focus group data collection methods. In light of these challenges, we propose two alternative approaches for collecting focus group data: (a) extended period of quantitative data collection that facilitated relationship building in the sites prior to qualitative focus groups and (b) focus groups by videoconference. We share our experiences on employing both of these approaches in two national research programs.